IEM-SAFE ELITE Magazine 2.0 - Kasumawati, Lias; Siti Noor Linda, Taib; Ervina, Junaidi (UNIMAS, 2023)
IEM-SAFE ELITE Magazine presents the activities organized by the IEM-SAFE UNIMAS Student Section. This is the second edition magazine of The IEM-SAFE UNIMAS Student Section, edited by Exco Media & Publicity. It consists of the information on the activities conducted by the IEM-SAFE UNIMAS Student Section.